Peran Program Teaching in Society Dalam Meningkatkan Motivasi Belajar Anak-Anak Desa Pasir Permit - Samin Lubis, Mara; Dongoran, Raisha Zuhaira; Salsalina Br Ginting, Iren (PT. Alahyan Publisher Sukabumi, 2024)
Learning motivation is an important factor in educational success, especially in rural areas where access to educational resources is often limited. One approach to overcome this problem is through a teaching program that involves student participation, such as what is done in the Real Work Lecture (KKN). The Teaching in Society program, which is part of KKN, seeks to help increase children's motivation to learn through engaging and participatory teaching. This study examines how the 19 KKN Group is able to contribute to increasing the learning motivation of children in Pasir Permit Village through this program.